2019
DOI: 10.1016/s2468-1253(19)30345-0
|View full text |Cite|
|
Sign up to set email alerts
|

The global, regional, and national burden of colorectal cancer and its attributable risk factors in 195 countries and territories, 1990–2017: a systematic analysis for the Global Burden of Disease Study 2017

Abstract: Background Data about the global, regional, and country-specific variations in the levels and trends of colorectal cancer are required to understand the impact of this disease and the trends in its burden to help policy makers allocate resources. Here we provide a status report on the incidence, mortality, and disability caused by colorectal cancer in 195 countries and territories between 1990 and 2017. Methods Vital registration, sample vital registration, verbal autopsy, and cancer registry data were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
201
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 308 publications
(207 citation statements)
references
References 38 publications
5
201
0
1
Order By: Relevance
“…Those estimates constitute an increase from 2018 to 2019 by 1330 and 1420 cases, respectively, ranking pancreatic cancer as the fourth most common cause of cancerrelated deaths in both American men and women [1,2]. Despite recent advances in cancer therapy worldwide, 5-year survival rates for pancreatic malignancies remain low, increasing only from 4% to 9% in the last 4 decades [3,4]. Thus, efforts are needed to understand the underlying causes of this disease, to improve the knowledge of its epidemiological features and to translate these findings into the management of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Those estimates constitute an increase from 2018 to 2019 by 1330 and 1420 cases, respectively, ranking pancreatic cancer as the fourth most common cause of cancerrelated deaths in both American men and women [1,2]. Despite recent advances in cancer therapy worldwide, 5-year survival rates for pancreatic malignancies remain low, increasing only from 4% to 9% in the last 4 decades [3,4]. Thus, efforts are needed to understand the underlying causes of this disease, to improve the knowledge of its epidemiological features and to translate these findings into the management of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer is the third most common cancer and is considered to be the second leading cause of cancer‐related mortality (Darband et al., 2020, Ghazizadeh Darband et al., 2020). According to recent statistics, there were ∼881,000 colorectal cancer‐related deaths worldwide in 2018 (Mirza‐Aghazadeh‐Attari et al., 2018; Safiri et al., 2019). In addition to various physical challenges for patients with colorectal cancer, these patients also present with a broad range of mental disorders, such as depression, anxiety, fatigue, pain and cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Besides chemical manipulation of the cell culture conditions, dysfunctional ECFCs could be primed by physical stimulation. For instance, a recent investigation revealed that farinfrared radiation [188] treatment rescued motility and tube formation in ECFCs isolated from type 2 diabetes mellitus patients by reducing the microRNA-134 (miR-134-5p) and consequently upregulating the nuclear receptor-interacting protein 1 (NRIP1) [193]. The same results were obtained on ECFCs exposed to high glucose (HG-ECFCs) [193].…”
Section: Priming Dysfunctional Ecfcs To Rescue Their Angiogenic Activitymentioning
confidence: 72%
“…Manipulation of the cell culture medium has also been exploited to rescue the angiogenic activity of dysfunctional ECFCs (Table 3). For instance, ECFCs derived from patients suffering from diabetes with neuroischemic (NI) or neuropathic [188] foot ulcers display delayed colony emergence, reduced proliferative potential and migratory activity, impaired tubulogenic activity and lower NO bioavailability [189]. Nevertheless, the glycomimetic C3 improved migration in both types of diabetic ECFCs, while it also rescued bidimensional tube formation in NI ECFCs [189].…”
Section: Priming Dysfunctional Ecfcs To Rescue Their Angiogenic Activitymentioning
confidence: 99%